Evaluasi Kebijakan dan Praktik Pengelolaan Mangrove di Paluh Kurau, Kecamatan Hamparan Perak, Sumatera Utara - Saputri, Ayu Surya; Manalu, Devi Rosalinda; Gultom, Windri P.; Harefa, Meilinda Suriani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The mangrove area in Paluh Kurau, Deli Serdang Regency, North Sumatra, plays a crucial role in climate change mitigation, coastal protection, and fishery resources. However, pressures from land-use conversion, overexploitation, and weak policy implementation threaten the sustainability of this ecosystem. This study aims to evaluate the effectiveness of mangrove management policies and practices in Paluh Kurau. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with stakeholders (local government, communities, NGOs, and academics), field observations, and analysis of relevant policy documents. The findings indicate that although several mangrove protection policies exist at the national and regional levels, their implementation in Paluh Kurau remains suboptimal. This study provides strategic recommendations for the government and stakeholders to improve sustainable mangrove governance.